Carbon nanotube alignment and sorting: Attempting a sulfur moiety as anchoring component. (3rd July 2019) - Kulak, Monika R.; Schipper, Derek J.
Abstract: Previously, the Schipper group established a method for simultaneously sorting and aligning single walled carbon nanotubes using an alignment relay technique (ART) with molecule 1 . Here, further synthetic investigations were pursued to explore another anchoring group and expand functionalization onto different surfaces, in particular for gold substrates. A thiophosphonate moiety (2 ) is attempted as a substitute for the phosphonate ester on 1 as sulfur has been shown to efficiently chemisorb onto gold surfaces and could make an interesting substrate pursuit for better carbon nanotube alignment. For 2 – it has potential to be obtained through the use of Lawesson's reagent, although currently the synthesis here failed to demonstrate isolation of the compound. Therefore, additional screening for different intermediate sulfur aligning molecules was also conducted, as to improve the density along side molecule 1 for ART applications. Outcomes are compared with the results on gold surfaces yielding from 1 to establish if more or fewer nanotubes are present on the surface in a horizontally aligned manner with respect to one another. Orientation is characterized via atomic force microscopy and chiralities of the nanotubes are observed via Raman spectroscopy. GRAPHICAL ABSTRACT: UF0001